Specialized Pediatric Palliative Care in Neonates with Life-Limiting Illness: A Systematic Review - Zuniga-Villanueva, Gregorio; Widger, Kimberley; Medeiros, Christina; Trenholm, Madeline; Streuli, Jürg C. (American Journal of Perinatology, 2020)
Objective The aim of this study is to assess the impact of specialized pediatric palliative care (PPC) on neonates with life-limiting conditions compared to standard care.Study Design MEDLINE, PsycINFO, Cochrane Central Register of Controlled Trials, Web of Science, CINAHL, Scopus, and Embase databases were searched from January 2000 to September 2018. Randomized clinical trials, experimental or observational studies, and secondary administrative database analyses published in English, Spanish, French, and German were included. Two independent reviewers extracted data, and used the Newcastle-Ottawa Scale and the Cochrane Risk of Bias Tool for quality analysis. Discrepancies were resolved as a team.Results From the 37,788 records obtained, only eight articles met the inclusion criteria. A meta-analysis was not possible due to the heterogeneity in how the outcomes were defined; however, a qualitative synthesis of the results was possible; organizing outcomes into eight different categories: psychological, social and spiritual support; communication; location of care; symptom management; bereavement care; predicted versus actual neonatal outcomes; and parental coping, stress, and satisfaction.Conclusion Specialized versus may have an impact on neonates with life-limiting conditions and their families. More studies that evaluate the impact of specialized versus in neonates with sound statistical analysis is warranted.
Keywords: palliative care; perinatal; life limiting; teams; outcomes